Analisa Kecepatan Pengelasan dan Kecepatan Putar Mata Pahat terhadap Konduktivitas Listrik Sambungan Aluminium dan Tembaga Hasil Friction Stir Welding (FSW) - Wikan Jatimurti; Fauzan Kurniawan; Budi Agung Kurniawan (Jurnal Engine: Energi, Manufaktur, dan Material, 2019)
The tool pin rotational speed and welding speed affect the electrical conductivity value of the Al-Cu connection. Al-Cu connection is a butt joint resulting from the friction stir welding (FSW) process. The material used is Al 6061 and pure copper. The friction stir welding (FSW) process uses a pin tool with a pin design that integrates with the pin tool and a three-degree angle. The purpose of this study was to determine the electrical conductivity value of the Al-Cu connection with the friction stir welding (FSW) process at the butt joint connection. The variables used in this study were pin tool rotation speeds of 800, 1000, and 1250 RPM and welding speeds of 10, 12.5, and 16 mm/min. Tests conducted in this study were macro structure testing, measurement of resistance values,  and microhardness testing. Besides, an analysis of heat input and welding time is needed for each variable. The results of macro and XRD structure test results show that in the aluminum and copper connection, there are intermetallic compounds in the form of AlCu and Al2Cu. The results of the analysis state that the welding results with a welding speed of 12.5 mm/min are the most optimum variables. The welding process results in conductivity values ranging from 27.173 mΩ-1mm-2 and 28.09 mΩ-1mm-2. The presence of intermetallic compounds affects the conductivity value of the connection.